Parental Personality, Relationship Stress, and Child Development: A Stress Generation Perspective. Issue 2 (21st May 2015) - Tang, Eileen; Luyten, Patrick; Casalin, Sara; Vliegen, Nicole
Abstract : This study aimed to investigate associations among the parental personality dimensions of self‐criticism and dependency, parental relationship stress, and child development from a stress generation perspective. Data from 79 first‐time parents and their children aged 8–13 months, who were followed up in a two‐wave, 1‐year longitudinal study, were analysed within a multilevel structural equation modelling framework in order to account for within‐couple interdependence. Results revealed that, as hypothesised, both parental self‐criticism and dependency were associated with increased levels of relationship stress, which in turn were negatively related to child development. Hence, parental personality features in combination with relationship stress may be an important target in couple and family‐based interventions. Implications for further research on family dynamics and interventions are discussed. Copyright © 2015 John Wiley & Sons, Ltd.